PERAN PENDIDIKAN KEPRAMUKAAN DALAM MEMBANGUN JIWA KEPEMIMPINAN PESERTA DIDIK DI MA SULAMUL HUDA SIWALAN MLARAK PONOROGO - Moch Abdi Muchlis; Nurul Iman; Ayok Ariyanto (Universitas Muhammadiyah Ponorogo, 2018)
Scouting education in the 2013 curriculum is extracurricular to be held in Schools / Madrasas. This aims to prepare young people who are expected to be able to become leaders with the character so that they can bring progress to the future. In scouting education is not only the theory that is delivered, but more applies the field practice that is packaged in the form of activities that are active, innovative, fun and contain character values needed in building the leadership spirit of students.This research was conducted with the aim to find out how the application of scouting education, how the role of scouting education in building the leadership spirit of students, and what are the supporting factors and obstacles to scout education in MA Sulamul Huda Siwalan Mlarak Ponorogo. The type of research used is descriptive qualitative with a field study approach and participant observation. In this study, researchers explored information from several speakers, including principals, scout advisers, scout coaches, and scout members. The data collection technique of this research was by interview, observation, documentation. Data analysis techniques used descriptive qualitative with interactive analysis consisting of three stages, namely data reduction, data presentation, and conclusion drawing. This research begins with the preparation, implementation, reporting activities.The results showed that the role of scouting education in building the leadership spirit of students in MA Sulamul Huda was very large. Scouting education is implemented based on a planned program, and is packaged in the form of interesting and fun activities to shape the character of students to be religious, disciplined, confident, honest, responsible, hard workings, tolerant, creative, independent, democratic, national spirit, friendly and communicative, love peace, care for the environment and social care. These values are applied in daily activities in Madrasas such as coming on time, keeping the call to prayer schedule, becoming dhuha and dzuhur prayer priests, imam tahlil, Takziah together when someone dies. From habituation makes students more mature in addressing all problems, able to become leaders (meetings / deliberations, ceremonies, prayer priests, and imam tahlil), then also discipline in entering the class, keeping the call to prayer schedule and active in muhadhoroh, independent in doing everything things, responsible for their words and actions, excited and cheerful in carrying out activities, honest and trustworthy, and broad-minded.